Implementation Of Continuous Wearable Low Power Blood Glucose Level Detection Using GSR Sensor - Mohd Saad, Wira Hidayat; Abd. Razak, Muhd. Shah Jehan; Tan, Yun Shen; Abd Salam, Nurul Akmal; Salehuddin, Fauziyah; Wong, Yan Chiew (2017)
Diabetes Mellitus is one of the most common life-threatening diseases in the world. The aim of this project is to implement a low power wearable system for continuously monitoring the glucose level in human blood by using GSR sensor. The development of non-invasive blood glucose level detector is desired to replace the invasive method which is inconvenient and expensive. This project is successfully detected the GSR value and establishing a correlation between GSR and the blood glucose level. It is clearly demonstrated that GSR can be useful in assisting to determine the blood glucose level as an alternative method for non-invasive approach. A correlation of 65.73% was found from the result and a threshold of (+-2V) for GSR data and it is identified for the end user to alert their blood glucose level. However, there are some factor such as dynamic movement, temperature and calories burnt might affect the accuracy and precision of the prototype.